(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides a comprehensive overview of the meanings, stages of development, and classifications of fatwas. It delineates the distinctions between a fatwa and a judicial ruling issued by a qadi, and details the qualifications necessary for a mufti. Additionally, it includes insights from the Companions and Tabi’un on the responsibilities and ethical considerations involved in issuing a fatwa.